2012
DOI: 10.1111/and.12034
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of seminal reactive nitrogen and oxygen species and total antioxidant capacity with sperm DNA fragmentation in infertile couples with normal and abnormal sperm parameters

Abstract: The objective of this study was to investigate the association between the amount of superoxide anion, peroxynitrite as oxidative stress (OS) markers and total antioxidant capacity (TAC) with sperm DNA fragmentation in infertile men with abnormal semen parameters. Semen samples were obtained from 102 infertile couples and divided into groups with normal and abnormal semen parameters according to the World Health Organization (WHO). Peroxynitrite and superoxide anions were detected using spectrofluorometric ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…Also, negative associations were found between ONOO 2 levels and Na + /K + -ATPase and Ca 2+ -ATPase activity, and total thiol content (Vignini et al, 2009). A positive correlation has also been reported between RNS and sperm DNA fragmentation (Khosravi et al, 2012). It has been suggested that ONOO 2 generation is the result of excessive activity of nitric oxide synthase and nitric oxide formation, which would cause the decreased sperm function observed in patients with varicocele (Mitropoulos et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, negative associations were found between ONOO 2 levels and Na + /K + -ATPase and Ca 2+ -ATPase activity, and total thiol content (Vignini et al, 2009). A positive correlation has also been reported between RNS and sperm DNA fragmentation (Khosravi et al, 2012). It has been suggested that ONOO 2 generation is the result of excessive activity of nitric oxide synthase and nitric oxide formation, which would cause the decreased sperm function observed in patients with varicocele (Mitropoulos et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…In asthenozoospermic infertile men, higher levels of ONOO 2 and nitration of the tyrosine residues have been found than in normospermic fertile men (Vignini et al, 2006;Salvolini et al, 2012). A negative correlation has been reported between ONOO 2 concentration and sperm morphology and motility (Vignini et al, 2006;Khosravi et al, 2012). Also, negative associations were found between ONOO 2 levels and Na + /K + -ATPase and Ca 2+ -ATPase activity, and total thiol content (Vignini et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Among the various causative agents unravelled, oxidative stress has always been concomitant with nonspecific DNA fragmentation [Aitken et al 2010;de Castro et al 2015;Iommiello et al 2015;Khosravi et al 2014;Muratori et al 2015;Noblanc et al 2013;Wright et al 2014]. This yields an atypical metabolically unbalanced state in which supra-physiological production of reactive oxygen species (ROS) overwhelms the impaired antioxidant defence.…”
Section: Introductionmentioning
confidence: 99%
“…Shapoval et al, 2003). Reactive oxygen forms can damage sperm compatibility and thus reduce their viability (Khosravi et al, 2014;Horký et al, 2012b). So the proper antioxidant system activity in the ejaculate plays an important role in keeping boars reproduction properties.…”
Section: Introductionmentioning
confidence: 99%
“…The other enzymes from antioxidant system which play an important role in boar ejaculate are: catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione transferase (GST) and phospholipid hydroperoxide glutathione peroxidase (PHGPx) (Koziorowska-Gilun et al, 2011;Horký, 2014). The antioxidants may improve ejaculate quality (Khosravi et al, 2014). The forms of reactive oxygen negatively affect the sperm quality and cause the lipid peroxidation (Ashrafi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%